Comparative evaluation of expression of proliferating cell nuclear antigen in variants of ameloblastoma and ameloblastic carcinoma - R Maya; B Sekar; S Murali (Wolters Kluwer Medknow Publications, 2012)
Aim: To evaluate the use of proliferating cell nuclear antigen index in the different histopathological variants of ameloblastoma, such as the follicular, plexiform, and unicystic types, and in ameloblastic carcinoma by immunohistochemical staining. The proliferating cell nuclear antigen index values of the variants of ameloblastomas and ameloblastic carcinomas are compared in order to determine the biological behavior of these tumors. Materials and Methods: For the present study, archival tissues that had been diagnosed as ameloblastoma and ameloblastic carcinoma were collected from the department of oral pathology. Specimens were embedded in paraffin wax and were sectioned at a thickness of 5 μm and stained with hematoxylin-eosin for reconfirming the histologic pattern. It was also stained immunohistochemically for anti-proliferating cell nuclear antigen antibody. Results: Positive proliferating cell nuclear antigen expression is seen as a light brown, granular stain. The proliferating cell nuclear antigen values of ameloblastic carcinoma were almost five times the value of ameloblastoma. Analysis of variance test, Fischer's exact test/variance ratio test, and Student's t-test were performed and the probability values were determined. Summary and Conclusion: This study showed that ameloblastic carcinoma had the maximum proliferative capacity. Among the variants of ameloblastoma, the plexiform variety had the maximum proliferative capacity, followed by the follicular and unicystic varieties. Altogether, these data indicate that proliferating cell nuclear antigen is related to the biological behavior and proliferation of tumor cells in the variants of ameloblastoma and ameloblastic carcinoma.